Can visuospatial measures improve the diagnosis of Alzheimer's disease?. Issue 1 (6th November 2017) - Salimi, Shirin; Irish, Muireann; Foxe, David; Hodges, John R.; Piguet, Olivier; Burrell, James R.
Abstract: Introduction: Overlapping and evolving symptoms lead to ambiguity in the diagnosis of dementia. Visuospatial function relies on parietal lobe function, which may be affected in the early stages of Alzheimer's disease (AD). This review evaluates visuospatial dysfunction in patients with AD, frontotemporal dementia, dementia with Lewy bodies, and vascular dementia to determine the diagnostic and prognostic potential of visuospatial tasks in AD. Methods: A systematic search of studies (1960–2016) investigating visuospatial dysfunction in dementia was conducted. Results: Tests measuring construction, specifically Block Design and Clock Drawing Test, and visual memory, specifically Rey‐Osterrieth Complex Figure recall and topographical tasks, show the greatest diagnostic potential in dementia. The Benton visual retention, Doors and People, and topographical memory tests show potential as prognostic markers. Discussion: Tests of visuospatial function demonstrate significant diagnostic and prognostic potential in dementia. Further studies with larger samples of pathologically confirmed cases are required to verify clinical utility. Highlights: Memory deficits have been demonstrated in Alzheimer's and non‐Alzheimer's dementias. Parietal lobes are uniquely affected in the early stages of Alzheimer's disease. Visuospatial tasks demonstrate significant diagnostic and prognostic potential. Computerized test protocols have been developed to test aspects of visuospatial function and memory. Novel topographical memory tasks demonstrated the greatest prognostic potential.